2011
DOI: 10.1111/j.1551-2916.2011.04563.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CaZrO3 on X8R Nonreducible BaTiO3‐BasedDielectric Ceramics

Abstract: Effects of CaZrO3 on BaTiO3–MgO–MnO2–Y2O3 nonreducible ceramics were investigated. The specimens modified by CaZrO3 in the range from 0 to2 mol% were prepared via conventional mixing method. Transmission electron microscopic analysis revealed that doping elements were enriched at grain boundaries and “core–shell” structures were formed. The addition of CaZrO3 could lower the sintering temperature. The Curie temperature was shifted to a higher point with increasing CaZrO3, attributed to the existence of an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Compared with the results in literature [14], the Tc was a bit higher after adding Yb 2 O 3 . On the basis of literature [15,16], it can be found that Yb 3? had the capability to elevate the Tc, especially co-doping with Bi 3?…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the results in literature [14], the Tc was a bit higher after adding Yb 2 O 3 . On the basis of literature [15,16], it can be found that Yb 3? had the capability to elevate the Tc, especially co-doping with Bi 3?…”
Section: Methodsmentioning
confidence: 99%
“…Due to keen market competition, low temperature co-fired technical ceramics (LTCC), with high permittivity and appropriate characteristics, are continuously demanded [1]. Several low firing BaTiO 3 based X8R ceramics such as BaTiO 3 -Nb 2 O 5 -Ni 2 O 3 [2], BaTiO 3 -Nb 2 O 5 -Co 2 O 3 -Bi(Mg 0.5 Ti 0.5 )O 3 [3], BaTiO 3 -MgO-MnO 2 -Y 2 O 3 -CaZrO 3 [4], (Ba,Bi)TiO 3 -Ba(Ti,Zr)O 3 [5], BaTiO 3 -Mn 3 O 4 -Bi 4 Ti 3 O 12 [6], etc., have been reported. However, most of the reported low firing BaTiO 3 based X8R ceramics show low dielectric constant (o2500), and the sintering temperatures are above 1200 1C, which is too high to be applicable to LTCC.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the effect of Li 2 O-Bi 2 O 3 -B 2 O 3 (for short LBBO) frit on phase composition, microstructure and dielectric properties of the K 0.5 Na 0.5 NbO 3 doped BaTiO 3 samples were systematically investigated. 4 , and Ba (Ac) 2 used in our experiment were analytical grade chemicals (with a minimum purity of 98%) obtained from the Shanghai Chemical Reagent Factory (Shanghai, China). We prepared BaTiO 3 powders via the sol-gel process [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is not only widely used as a conventional ferroelectric but also recently introduced in components of MLCCs [4].However, the sharply change in dielectric constant at Curie temperature(125˚C) of pure BT has limited its application to a relatively narrow using temperature range. Previous studies have demonstrated that to own a stable temperature coefficient of capacitance (TCC), an effective method is to shift Curie temperature(T c ) to a high temperature [5]. It is reported that T c is increased effectively by doping high T c value substances and ion substitution.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that T c is increased effectively by doping high T c value substances and ion substitution. Firstly, BaTiO 3 can be modified by many dopants with high T c value e.g., Bi 2 O 3 ,(Bi 0.5 Na 0.5 )TiO 3 ˈ K0.5Na0.5NbO3ˈ et al, to obtain a broadened TCC curve with dielectric constant declining significantly [5,6].In order to obtain a high dielectric properties, it is used to doping lead elements in barium titanate, such as Pb 3 O 4 , , Pb(Ti,Sn)O 3 , PbTiO 3 , PZT [7,8].…”
Section: Introductionmentioning
confidence: 99%